Facilitators and barriers to colorectal cancer screening using the immunochemical faecal occult blood test among an average-risk population in semi-rural Malaysia: A qualitative study. - Kogila Ramanathan; Désirée Schliemann; Nor Saleha Binti Ibrahim Tamin; Devi Mohan; Michael Donnelly; Tin Tin Su (PLoS ONE)
Background Colorectal cancer (CRC) incidence in Malaysia is increasing, and most CRC patients are diagnosed at a late stage. This study investigated participant awareness of CRC and their perceptions and views about CRC screening, barriers, benefits, and facilitators towards CRC screening participation as well as health-seeking behaviour and the use of preventative health services. Method Eleven focus group discussions (FGDs) were conducted with a purposive sample of 89 participants aged > 50 from the major ethnic groups in the Segamat District, Johor State. FGDs were audiotaped, transcribed verbatim, and translated into English. Data were analysed using thematic analysis. Results We identified trust in doctors as a key reason for whether or not to seek health care. Generally, the participants had low awareness of CRC sign/symptoms and screening. Emotional and logistic concerns about sending a stool sample to a clinic emerged as the main barriers to screening. Simplified illustrated instructions about stool collection in Malay, Chinese and Tamil, free screening at health clinics and reminders to complete the iFOBT test were perceived to facilitate engagement in screening, and posited as strategies that were likely to increase iFOBT uptake. Conclusion Primary care physicians play a crucial role in terms of reducing patient's misperceptions, recommending screening to patients, enhancing attendance, and improving uptake of CRC screening. There is a need for further research to investigate ways in which to reduce identified barriers and implement and test potential facilitative strategies as well as examine adherence by doctors to clinical guidelines about CRC screening.